2016
DOI: 10.1002/alr.21789
|View full text |Cite
|
Sign up to set email alerts
|

Primary immunodeficiency and recalcitrant chronic sinusitis: a systematic review

Abstract: Patients with recalcitrant CRS should be evaluated for primary immunodeficiency. This should include as assessment of quantitative serum immunoglobulin levels as well as functional antibody responses. Medical therapy, particularly immunoglobulin replacement therapy, appears to be most effective when administered at high doses early in the disease course. The addition of surgery is less clearly supported, but may also provide benefit if performed early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
(88 reference statements)
0
26
0
5
Order By: Relevance
“…Immunodeficiencies such as common variable immune deficiency (CVID), X-linked agamaglobulinmia (XLA) and specific antibody deficiency (SAD) may also contribute to difficult control of CRS as well, which should be taken into consideration in future study design. 82,83 …”
Section: Identification Of Crs Endotypes By Clustering Analysismentioning
confidence: 99%
“…Immunodeficiencies such as common variable immune deficiency (CVID), X-linked agamaglobulinmia (XLA) and specific antibody deficiency (SAD) may also contribute to difficult control of CRS as well, which should be taken into consideration in future study design. 82,83 …”
Section: Identification Of Crs Endotypes By Clustering Analysismentioning
confidence: 99%
“…Serious sinus infections (more than 2 in childhood and 4 in adulthood) within 1 year are 1 of the 10 warning signs of PID proposed by the Jeffrey Modell Foundation [14]. Chronic sinusitis is very frequent in PID patients [15], although this frequency varies with the type of study and PID, as shown in a systematic review where 10%-54% of patients with chronic sinusitis had PID [16]. We previously demonstrated that sinusitis was the most common ear, nose, and throat presentation in patients with primary antibody deficiency (PAD) [17].…”
Section: Sinusitismentioning
confidence: 99%
“…Его частота не велика (0,1 -0,4%), но его возникновение нередко требует повторных операций [1,2,4,8]. При выполнении органосохраняющих операций по поводу эхинококкоза печени это осложнение может возникнуть при повреждении желчных протоков, при не тщательном ушивании желчных свищей открывающихся в полость кисты, а после радикальных при недостаточно полном холестазе [2,5,6,10].…”
Section: Introductionunclassified
“…Достоверно увеличена концентрация IL-1β, IL-8, TNFα, INFγ. Провоспалительные цитокины поддерживают реакцию воспаления, усиливают интоксикационный симптом за счет стимуляции цитотокситности лимфоцитов [1,2]. IL-1β запускает и поддерживает реакции воспалительно-регуляторного каскада.…”
unclassified